DINAMIKA GENERASI SANDWICH: IMPLIKASI TERHADAP KEPUTUSAN MENUNDA PERNIKAHAN DALAM PERSPEKTIF ISLAM (STUDI KASUS PADA MAHASISWA UNIVERSITAS INSAN CITA INDONESIA): - - Rahma Dwi Pratiwi, Amelia; Kumaini, Ruston (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
The sandwich generation faces complex dilemmas between family responsibilities and personal aspirations, including marriage decisions. This study aims to identify factors causing marriage delay among sandwich generation students at Universitas Insan Cita Indonesia and analyze them from Islamic perspective. The research employed qualitative case study approach with in-depth interviews of students aged 20-30 years. Data analysis used triangulation from Al-Qur'an, hadith, four imam schools, maqashid syariah.. Results identified four main factors: economic pressure requiring respondents to bear 70-80% of family needs, difficulty finding partners who understand sandwich generation conditions, concerns about creating new sandwich generation, and emotional-mental unpreparedness. From Islamic perspective, marriage delay can be justified through syariah principles as efforts to establish readiness. The study concludes that marriage delay represents rational response aligned with Islamic syariah principles. Special support programs and contextual Islamic marriage education are needed to accommodate sandwich generation needs.